Screening for Protein-Protein Interaction Inhibitors Using a Bioluminescence Resonance Energy Transfer (BRET)–Based Assay in Yeast. (July 2017) - Corbel, Caroline; Sartini, Sara; Levati, Elisabetta; Colas, Pierre; Maillet, Laurent; Couturier, Cyril; Montanini, Barbara; Bach, Stéphane
The bioluminescence resonance energy transfer (BRET) technology is a widely used live cell-based method for monitoring protein-protein interactions as well as conformational changes within proteins or molecular complexes. Considering the emergence of protein-protein interactions as a new promising class of therapeutic targets, we have adapted the BRET method in budding yeast. In this technical note, we describe the advantages of using this simple eukaryotic model rather than mammalian cells to perform high-throughput screening of chemical compound collections: genetic tractability, tolerance to solvent, rapidity, and no need of expensive robotic systems. Here, the HDM2/p53 interaction, related to cancer, is used to highlight the interest of this technology in yeast. Sharing the protocol of this BRET-based assay with the scientific community will extend its application to other protein-protein interactions, even though it is toxic for mammalian cells, in order to discover promising therapeutic candidates.